2021
DOI: 10.7498/aps.70.20201816
|View full text |Cite
|
Sign up to set email alerts
|

A second-order gradiometric superconducting quantum interference device current sensor with cross-coupled structure

Abstract: Superconducting quantum interference device (SQUID) has extremely high magnetic field sensitivity, current sensitivity, and can detect a low-noise weak current signal. The SQUID current sensor has become the only option of the readout of low-noise detector, such as transition-edge sensor (TES). In this paper, a second-order gradiometric cross-coupled SQUID current sensor for TES application is developed. According to the requirements for TES detectors, the structure and various parameters of SQUID current sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The designed second-order gradient overlap-coupling octagonal structure is different from that in our previous work [15]. The cross-coupling octagonal structure reported in [15] adopts a slot washer in the superconducting loop and an input coil of 2.5 turns. However, the overlap-coupling octagonal structure in this work uses a whole washer without slots and input coils of 1.5, 2.5 and 5.5 turns.…”
Section: Designmentioning
confidence: 91%
See 3 more Smart Citations
“…The designed second-order gradient overlap-coupling octagonal structure is different from that in our previous work [15]. The cross-coupling octagonal structure reported in [15] adopts a slot washer in the superconducting loop and an input coil of 2.5 turns. However, the overlap-coupling octagonal structure in this work uses a whole washer without slots and input coils of 1.5, 2.5 and 5.5 turns.…”
Section: Designmentioning
confidence: 91%
“…We developed a first-stage second-order gradient SQUID design referred to the SQUID designs reported in the literature [2][3][4]15]. This is intended to operate at temperatures from 4.2 K to mK for the readout of TES detectors.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…A SQUID based on second-order gradiometric design has been developed. The initial results showed that the flux white noise is about 2 μΦ0/√Hz at 4.2 K with an input current sensitivity of 17 μA/Φ0 24 . A SQUID array based on 16 first-order gradiometric SQUID cells has also been developed.…”
Section: Squid and Multiplexing Readout Electronicsmentioning
confidence: 99%